The Impacts of Consumptive Behaviors toward American Society in Modern Era as Reflected in the Film The Joneses - Ambarwati Budi Rahayu; Nadella Lesmana; Didik Murwantono (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
In this research, the writers make research of consumptive behavior and its impacts. “The Joneses” film represents the impacts of consumptive behavior in American society in many aspects of life. The objective of this paper is to describe and find the impacts of consumptive behavior toward American society, as reflected in the film "The Joneses." In analyzing data, the writers use a qualitative method by gathering the data qualitatively. The result reveals kinds of consumptive behavior, factors of consumptive behavior, impacts of consumptive behavior, and things that influence consumptive behavior. Some of them are environment and internal motivation.